REYKJAVÍK DECLARATION 2004 On the occasion of the 4th Ministerial Meeting of the Arctic Council - Arctic Council, - (Arctic Council, 2004)
REYKJAVÍK DECLARATION On the occasion of the Fourth Ministerial Meeting of the Arctic Council, 24 November 2004 in Reykjavík, Iceland.